Development and Measurement COVID-19 Reminder Hat with Ultrasonic Sensor HC-SR04 - Barry Nur Setyanto; Filly Pravitasari; Pramudita Budiastuti; Fanani Arief Ghozali (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2022)
The development of ultrasonic sensor technology used for suitable equipment is widely carried out, such as distance sticks for the blind, floor cleaning robots, automatic garbage boxes, height measuring instruments, water volume detectors, automatic dispensers, automatic hand sanitisers, etc. In the study, the researchers developed a precision device based on an ultrasonic sensor called the COVID-19 reminder hat. The research design method is research and development, using the Borg and Gall approach. COVID-19 reminder Hat was developed using Arduino nano v3, battery, buzzer, and ultrasonic sensor HC-SR04. The product design was registered with Intellectual Property in the Industrial Design category with registration number A00202102408. The measurement distance of the ultrasonic sensor on flat objects shows an average error percentage of 2.64% from 10 cm to 300 cm with a range of 10 cm. Tests on irregular objects (humans) at an angle of zero degrees and 15 degrees showed an error at a distance of more than 200 cm and stable at a distance of 150 cm. So that 150 cm is the best distance to apply to the COVID-19 reminder hat. The development results show that the product is ready to be continued in the production and sales process.